EFFICIENCY OF DEMONSTRATION METHOD THROUGH ZOOM MEETING TO IMPROVE STUDENT'S COGNITIVE ABILITY IN ISLAMIC RELIGIOUS EDUCATION LEARNING (PAI) - Diana; Jalaluddin; Agus kenedi (Journal of Islamic Education and Learning, 2021)
Distance learning or online learning is currently the main choice in the process of teaching and learning activities. In the world of education, the growth of distance education or online learning technology has brought new colors and patterns. This condition is further strengthened by the development of learning through the use of technology that does not force students to gather in large groups and is limited by time and place. Therefore, the use of the Zoom Meeting application as an educational application is an alternative in learning. This zoom app helps students and teachers to teach. Whether it's far or away, a zoom meeting app can help streamline the learning process. The purpose of this study was to determine the efficiency of the demonstration method through zoom meetings to improve students' cognitive abilities in PAI learning. This research is a qualitative research, namely library research that uses books and other literature as the main topic. The results of the study suggest that learning to use zoom meetings in developing children's cognitive aspects does not always run smoothly, in fact there are many obstacles. Learning that is emphasized by direct experience is difficult to apply. Children who really need direct assistance from parents and teachers. Teachers only monitor online without being able to interact directly with children. The obstacles faced in implementing learning through zoom meetings are the limitations of students in possession of smartphones, knowledge of information technology, difficult signal networks, and student activity in learning